Recording body temperature in koalas (Phascolarctos cinereus): a comparison of techniques. Issue 8 (26th July 2018) - Adam, D; Beard, L; Johnston, SD; Nicolson, V; Lisle, A; McKinnon, A; Larkin, R; Theilemann, P; Gillett, A; Brackin, K; FitzGibbon, S; Barth, B; et al.
Abstract : Objective: Compare the use of four techniques to measure body temperature in koalas: intraperitoneal (thermal data logger and temperature sensitive radio transmitter), rectal (certified thermometer), tympanic (infrared thermometer), and hind foot (infrared camera). Methods: The body temperature data collected concurrently from the intraperitoneal loggers were used as the benchmark in the analyses. Results: The rectal, foot and tympanic methods consistently recorded lower body temperature when compared with the benchmark. There was a strong positive relationship (R 2 = 0.79) between logger and rectal measurements, but no significant relationship between logger and foot or logger and tympanic measurements. Conclusion: Rectal measurements can be used to record internal body temperature, with the caveat that such measurements will generally register a temperature approximately 0.25°C lower than the actual intraperitoneal temperature.